How to speak and vocal hygiene - Aimen Wasay; Muhammad Sikander Ghayas Khan; Khadija Saleem (Journal of the Pakistan Medical Association, 2022)
An abnormal tongue shape, pitch difference or voice quality can lead to difficulty communicating effectively. Common among teachers are voice issues, which can be uncomfortable and make it challenging to carry out daily tasks and work-related activities. 1 Teacher who suffers from voice disorders may have trouble communicating clearly with their students. Voice disorders affect negatively a teacher's ability to communicate effectively throughout the day and their emotions, leading them to feel inadequate and frustrated at times. Voice misuse is inappropriate voice usage. It includes speaking involving hard glottal attacks and cheerleading for an extended period. 2 Vocal abuse is defined as activities having a detrimental effect on the larynx and voice. These include yelling and screaming, excessive talking or singing, excessive talking with an upper respiratory infection or allergy. It is important to identify and reduce the phono traumatic behaviours (for example loud voice use, speaking over background noise, throat clearing, cheering and screaming, and unconventional voice production), awareness about the vocal mechanism, and address high-risk situations associated with speech. In addition, it involves controlling how much you talk, monitoring your pitch and intensity (The speech of a typical adult male will have a basic frequency from 85 to 155 Hz, and a typical adult female ranges from 165 to 255 Hz.) 3 and conserving your voice by resting it. A healthy voice is dependent upon several factors, including local lubrication (About 15.5 cups (3.7 litres) of fluids per day are recommended for men. 11.5 cups (2.7 litres) of fluids per day is recommended for women)4, necessary dietary choices; as well as eliminating the effect of medications, environment, and healthy lifestyle choices (reduction of alcohol, recreational drugs, tobacco, and caffeinated beverages,). 5.Voice hygiene has two primary goals: to improve communication effectiveness and to promote vocal health. Additionally, by fostering optimal vocal habits as a precautionary measure, your voice will be maintained healthily, reducing the risk of vocal injury. Voice hygiene awareness can help all professionals, especially teachers, to maintain voice quality. We believe regular voice use is a right of every individual, and understanding is needed to make people aware of voice disorders and how to prevent them. As professionals, we can assist and help out people with voice disorders or professionals at risk of acquiring voice disorders to rule out possible causes and treatment strategies.